2022
DOI: 10.3390/metabo12030226
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic Effects of PCSK9: Focus on Thrombosis and Haemostasis

Abstract: The proprotein convertase subtilisin/keying 9 (PCSK9) is a serine protease that has gained importance in recent years as a drug target, mainly due to its effect on cholesterol metabolism in promoting the degradation of the low-density lipoprotein receptor (LDLR). However, this protease may also play an important role in lipid-independent reactions, including the process of thrombogenesis. Considering this, we reviewed the effects and implications of PCSK9 on platelet function and blood coagulation. PCSK9 knock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 116 publications
(142 reference statements)
0
10
0
Order By: Relevance
“…In another study, D-dimer and fibrinogen concentration changes were not observed in patients with familial hypercholesterolemia. On the other hand, a reduction in plasma PAI-1 levels was documented [ 39 , 40 ]. Additionally, PCSK9 inhibitors raised HDL cholesterol concentrations [ 41 ], which may prevent platelet aggregation directly or indirectly by lowering platelet membrane cholesterol [ 42 ].…”
Section: Platelet Activation Markers and Pcsk9 Inhibitorsmentioning
confidence: 99%
“…In another study, D-dimer and fibrinogen concentration changes were not observed in patients with familial hypercholesterolemia. On the other hand, a reduction in plasma PAI-1 levels was documented [ 39 , 40 ]. Additionally, PCSK9 inhibitors raised HDL cholesterol concentrations [ 41 ], which may prevent platelet aggregation directly or indirectly by lowering platelet membrane cholesterol [ 42 ].…”
Section: Platelet Activation Markers and Pcsk9 Inhibitorsmentioning
confidence: 99%
“…The intriguing point remains whether inclisiran would provide an even stronger benefit on CV morbidity and mortality, compared to PCSK-9 inhibition by mAbs, due to the fact that in contrast to anti-PCSK9 mAbs, which are directed against circulating PCSK9, inclisiran inhibits PCSK9 synthesis intracellularly, thereby potentially having additional effects beyond modulation of LDL-R expression. Indeed, PCSK9 has a variety of pleiotropic effects, including involvement in inflammatory pathways or thrombogenesis [ 63 ]. On the other hand, theoretically, one could speculate that mAbs lead to a more complete inactivation of PCSK9, since they bind to all circulating PCSK9, including that generated by other organs like, e.g., intestine, endocrine pancreas, or the brain [ 64 •], whereas inclisiran only inhibits intracellular hepatic biosynthesis of PCSK9.…”
Section: Pcsk9 Inhibition: Critical Issues and Appropriate Therapy Al...mentioning
confidence: 99%
“…4 ). 22 This action is amplified in the presence of LDL-C. 99 It might be responsible for platelet hyperreactivity in dyslipidemia 100 and further initiates activation of multiple CD36-downstream signaling pathways. These include Scr, ERK5, JNK, increased generation of ROS, and activation of p38/cPLA 2 /COX-1/TXA 2 -signaling pathways.…”
Section: Pcsk9 and Platelet Activation—antagonism By Aspirinmentioning
confidence: 99%
“…Genetic studies have identified the serin protease proprotein convertase subtilisin/kexin type 9 (PCSK9) as the most relevant regulator of LDL-C receptor availability. In addition to its effect on LDL-C plasma levels, PCSK9 has also pleiotropic action beyond this, [17][18][19][20][21][22] including direct stimulatory actions on platelets 23 with platelets as a source of PCSK9 in coronary artery disease (CAD). 24 The finding that the effects of PCSK9 on platelet activation are inhibited by aspirin in vitro 25 underlines the possible synergistic effects between PCSK9 antibodies and aspirin and clearly favors these compounds over statins with their therapeutic limitations as discussed above.…”
Section: Introductionmentioning
confidence: 99%